UPDATE MANAGEMENT DENGUE SHOCK SYNDROME IN PEDIATRIC CASES - Soegijanto, Soegeng; Chilvia, Eva (Indonesian Journal of Tropical and Infectious Disease, 2013)
Background: Since 1968 Dengue Virus Infection has been found in Indonesia, especially at Surabaya and Jakarta city. Firstly management of dengue virus infection very difficult to improve, therefore the higher mortality nearly 41,4% had been found but on the following years in five decades the mortality rates was becoming to decrease until 1,27% on 2011. Aim: To find the new management of Dengue Shock Syndrome to reach the lower fatality rate below 1%. Method: Until now to manage Dengue Shock Syndrome is very difficult, some cases can be improved but the other lost due to the late coming in the hospital and not involved in criteria diagnosis base on WHO 1997. To solve this problem WHO 2009 had made new criteria diagnosis Dengue Virus Infection focusing on early detection of severe Dengue Virus Infection especially Dengue Shock Syndrome. Result: On 2011 WHO had made an integrated criteria diagnosis base on WHO 2009 and WHO 1997. These criteria was focusing in Update management of Dengue Shock Syndrome in Pediatric Cases. Based on this action, this paper will improve clinical management to reach the lower mortality of Dengue Shock Syndrome in Community until CFR < 1%. Conclusion: By using integrated criteria of WHO 2009 and 1997, update management of Dengue Shock Syndrome in Pediatric cases, can improve clinical management to reach the lower mortality in community until CFR < 1%.